Integrating Education, Technology, and Suistanable Practices for Community Empowerment in Siponjot Village - Zahedi; Dian Marisha Putri; Katrin Jenny Sirait; T. Irmansyah; Dolly Sojuangan Siregar; Miswar Budi Mulya; Benny Hidayat; Muhammadin Hamid; M. Sabri; Badai Charamsar Nusantara; Meutia Nauly (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study explores the implementation of a holistic community service program in Siponjot Village, North Sumatra, aimed at enhancing non-formal education, economic sustainability, and environmental resilience. Through the "Marsiajar Manang Didia Pe" initiative, the program promotes a flexible learning system aligned with local cultural values, addressing gaps in formal education. Key components include training in agricultural practices focusing on coffee and mahogany cultivation alongside the introduction of data-driven decision making tools such as economic mathematical models and QR codes for improved information management. Results indicate improved community engagement, increased agricultural productivity, and enhanced digital literacy. The findings highlight the critical interplay between education, technology adoption, and sustainable practices in fostering community empowerment and resilience against environmental challenges.